Analysis of Storage and Packaging Conditions on Physicochemical Characteristics of Eggplant (Solanum melongena L.) - Adhamatika, Adhima; Meidayanti, Karina; Indraloka, Aldy Bahaduri (Department of Agro-industrial Technology, University of Brawijaya, 2022)
AbstractEggplant (Solanum melongena L.) is a horticultural product widely distributed in Indonesia and is an easily damaged commodity during storage. Suitable storage conditions are needed to increase the eggplant's shelf-life. This study aims to determine the differences and the best conditions of packaging type, storage temperature, and shelf-life to maintain and improve the eggplant's quality. This research was conducted using a Nested Design with three replications. The analysis used includes weight loss, moisture content, ash content, pH, firmness level, protein content, fat content, and carbohydrates content. The results indicate that storage at cold temperatures (±8 °C) can inhibit metabolic processes, so there is a decrease in protein and carbohydrate content due to lower respiration processes than eggplant stored at room temperature (±27 °C). The type of polyethylene (PE) plastic packaging can reduce the potential for damage to eggplant during storage and increase the eggplant's shelf-life compared to brown kraft paper bag packaging and without packaging, which is characterized by better weight loss, protein, carbohydrates, and texture. Storage treatment for five days at cold temperatures (±8 °C) with PE plastic packaging was the best treatment in this study.Keywords: eggplant, packaging, storage, temperature Abstrak Terung (Solanum melongena L.) merupakan produk tanaman hortikultura yang sudah banyak tersebar di Indonesia dan merupakan komoditas yang mudah mengalami kerusakan selama penyimpanan. Kondisi penyimpanan yang sesuai dibutuhkan untuk meningkatkan umur simpan terung. Penelitian ini bertujuan mengetahui perbedaan dan kondisi terbaik penggunaan jenis kemasan, suhu penyimpanan, dan umur penyimpanan untuk mempertahankan dan meningkatkan kualitas terung. Penelitian ini dilakukan menggunakan Rancangan Nested dengan tiga kali ulangan. Analisa yang digunakan dalam penelitian ini meliputi analisa susut bobot, kadar air, kadar abu, pH, kekerasan, protein, lemak, dan karbohidrat. Hasil dari penelitian ini menunjukkan bahwa penyimpanan pada suhu dingin (±8 °C) dapat menghambat proses metabolisme sehingga terjadi penurunan kandungan protein dan karbohidrat yang disebabkan proses respirasi lebih rendah dibandingkan terung yang disimpan pada suhu ruang (±27 °C). Jenis kemasan plastik polyethylene (PE) mampu menurunkan potensi kerusakan terung selama penyimpanan dan meningkatkan umur simpan terung dibandingkan kemasan kraft paper bag cokelat dan tanpa kemasan yang ditandai hasil susut bobot, protein, karbohidrat, dan tekstur yang lebih baik. Perlakuan penyimpanan lima hari pada suhu dingin (±8 °C) dengan kemasan plastik PE merupakan perlakuan terbaik pada penelitian ini.Kata kunci: pengemasan, penyimpanan, suhu, terung